Model Iklim Kelas yang Dapat Mensejahterakan Siswa Pada Tingkat Pendidikan Dasar - Gazali, Munawir; Azizi, Asrorul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The students’ well-being is an educational issue that has recently received great attention from various parties, be they academicians, politicians, and policymakers. This research aimed to test the role of classroom climate in enhancing students’ well-being. A correlational study in our work revealed that overall, among a sample of 300 grade V and grade VI students in elementary schools and madrasah ibtidaiyah in Praya Lombok Tengah, classroom climate positively and significantly predicted students’ well-being. The classroom climate promoted students’ well being particularly when it took shape via task orientation and when it encouraged solidarity, cooperation, and involvement among students, as well as the perceived teacher justice. Aspects of classroom climate which were suboptimal in explaining students’ well-being included teacher support and learning inquiry.